Performance Measurement through Monitoring System to Achieve Organizational Targets - Nurdina Rahmi; Lina Suryani; Nahda Qonita; Dheanty Bilqis (Samudra Publisher, 2025)
Performance assessment is a crucial element in organizational management oriented toward achieving strategic objectives. One effective approach to ensuring the attainment of these goals is through a structured and continuous monitoring system. This study aims to analyze the role of monitoring systems in measuring and improving organizational performance in order to meet predetermined targets. A qualitative approach was employed using literature review and descriptive analysis of various theories, models, and previous research related to monitoring systems and organizational performance. Data sources were derived from scholarly journals, professional agency reports, and organizational policy documents. The findings indicate that a well-designed monitoring system can enhance transparency, accountability, and the effectiveness of decision-making processes within organizations. Both preventive and corrective monitoring serve as strategic instruments to minimize deviations, identify operational obstacles, and foster a results-oriented work culture. The system also plays a pivotal role in bridging strategic planning and operational execution through continuous monitoring mechanisms and evaluation based on key performance indicators (KPIs). Therefore, a monitoring system is not merely an internal control tool but also an integral part of strategic management that is adaptive and responsive to external environmental dynamics. The implications of this study highlight the importance of leadership, information technology, and organizational culture in supporting the implementation of an effective monitoring system. Recommendations emphasize the need to strengthen policy frameworks and integrate monitoring throughout the performance management cycle to achieve sustainable performance improvement.